Bicolumnar 90-90 Plating of Low-Energy Distal Humeral Fractures in the Elderly Patient. (September 2014) - Leigey, Daniel F.; Farrell, Dana J.; Siska, Peter A.; Tarkin, Ivan S.
Fragility fractures of the distal humerus in elderly patients, especially the low transcondylar fracture pattern, can be difficult to optimally manage. Although the fractures are typically low energy resulting in either extra-articular or simple intra-articular patterns, gaining fixation into the distal fragments can be difficult with open reduction internal fixation (ORIF) using traditional 90-90 or parallel plating techniques. Anatomy preserving reconstruction with ORIF is preferred over total elbow arthroplasty (TEA) if possible. In this study, 15 patients were managed with a bicolumnar 90-90 plating construct as a novel method of enhancing distal fixation in these fractures. Fourteen patients went on to radiographic union at an average of 77 days after surgery with an average arc of motion of 105°. One patient was lost to follow-up. Bicolumnar 90-90 plating of distal humerus fractures in elderly patients may represent a viable alternative to traditional ORIF or TEA.